Analisis dan Strategi Komunikasi Perancangan Program Edutainment “Seri Aktivitas Alam: Gunung Meletus” - Andreas James Darmawan; Dyah Gayatri Putri (Humaniora, 2015)
The process of visual communication strategies can be created into a good persuasive invitation. This study depicted the issues in the world of children when dealing with nature activity within the scope of volcano eruptions. This study was conducted with a qualitative approach and triadic, ethnographic in children psychological and behavioral conditions after volcanic eruption disaster. Research found the common thread between supporting and main theory related to visual communication strategies. It, then, described in detail the development of communicators to become a mascot, continued on the delivery of messages through the comics, and invited the target to experience design experience.